2020
DOI: 10.1021/acs.energyfuels.0c01776
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Fluid Development on a Chip for Renewable Energy

Abstract: From physical property measurement to modelling pore-scale environments, the study of fluids at the microscale is key to understanding and optimizing fluids for large-scale energy applications. Silicon-glass microfluidics is now a proven technology for chemical effectiveness testing in the conventional oil and gas energy sector. We see potential to apply microfluidic fluid characterization technology to renewable sectors, such as geothermal and solar thermal energy recovery where fluid customization is central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Glass microflow chips are usually used for microvisualization. PPNs were processed on high boric acid glass via wet etching and low-temperature bonding technology in Highray Chip Technology Co., Ltd. The glass-PPNs #I, #II, and #III were processed using core CT scan images as templates, as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Glass microflow chips are usually used for microvisualization. PPNs were processed on high boric acid glass via wet etching and low-temperature bonding technology in Highray Chip Technology Co., Ltd. The glass-PPNs #I, #II, and #III were processed using core CT scan images as templates, as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we utilized a microfluidic platform to address the question of PCS applicability and function at relevant shear rates (up to 300 s −1 ) and temperatures (up to 80 °C) during flow cycling employing the pressure drops 0.5−5.0 MPa in 0.5 MPa steps. 24 The PCS undergoing flow cycling and phase change can be visualized directly on the microfluidic platform, as seen in static (Figure 6a) and dynamic (Figure 6b) conditions. Figure 6a depicts the behavior of a PCS at 20 and 80 °C when there is no flow in the microchip (representing stagnant conditions).…”
Section: Microscale Analysismentioning
confidence: 99%
“…21 A particular challenge that PCMs present in flowing heat transfer applications is solidification on surfaces, reducing efficiency and lifetime. 23 It is observed that a PCM-based slurry exhibited severe coalescence upon transition from solid to liquid under operational conditions 24 and the breaking of PCS emulsions under thermal cycling. 25 These issues may be overcome by encapsulating the PCM with an additional material, often made from synthetic or natural polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Performing analyses using small volumes of fluid presents many advantages: heterogeneous systems manipulation with greater precision, smaller sample sizes and reagent volume requirements, and rapid high-throughput data collection. 22 Microfluidic measurements have been applied broadly in chemical, biological, and physical processes that are relevant to sensing, such as glass micromodels, capillary electrophoresis, and gas chromatography. In the area of f luid property measurement, microfluidics has enabled high accuracy measurements of phase and thermophysical properties such as bubble and dew points, 23−25 solution gas-oil ratios, 26 solubility and diffusivity, 27−30 minimum miscibility pressures, 31,32 wax crystallization, 33,34 and asphaltenes precipitation.…”
Section: ■ Introductionmentioning
confidence: 99%